2015
DOI: 10.24135/teacherswork.v11i2.69
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Effects of Mindfulness in Five Primary Schools in New Zealand

Abstract: This study investigated the effects of an eight-week mindfulness in schools

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…It is also considered as an intrinsic process that stresses his/her awareness of both internal and external experiences as they happen (Brown and Ryan, 2003). As stated by Rix and Bernay (2014), mindfulness is the full attention of an individual on what is occurring inside and nearby him/her both physically and mentally. The concept is important in the second/foreign language education context in which teachers in this job are pressurized from different angles such as emotionalaffective sides and environmental-professional sides.…”
Section: Introductionmentioning
confidence: 99%
“…It is also considered as an intrinsic process that stresses his/her awareness of both internal and external experiences as they happen (Brown and Ryan, 2003). As stated by Rix and Bernay (2014), mindfulness is the full attention of an individual on what is occurring inside and nearby him/her both physically and mentally. The concept is important in the second/foreign language education context in which teachers in this job are pressurized from different angles such as emotionalaffective sides and environmental-professional sides.…”
Section: Introductionmentioning
confidence: 99%
“…Next, the cultivation of mindfulness is targeted at school teachers, at both the preservice and in-service level, in an effort to: help ease teacher stress and burnout (Bernay, 2012(Bernay, , 2014Emerson, Leyland, Hudson, Rowse, Hanley, & Hugh-Jones, 2017;Jennings & DeMauro, 2017;Lomas, Medina, Ivtzan, Rupprecht, & Eiroa-Orosa, 2017); prepare student teachers for the workforce (Bernay, 2014;Poulin, 2009;Lomas et al, 2017;Soloway, 2017); enhance resilience and general wellbeing (Bernay, 2012(Bernay, , 2014; bring authenticity to the role of teaching (Bernay, 2012(Bernay, , 2014 and contribute to teacher professional development (Rix & Bernay, 2014).…”
Section: Mindfulness Educationmentioning
confidence: 99%
“…Drawings can provide a vehicle for students to "…think about, reflect and actually see their experiences" (Cohen-Miller, 2018). Several research studies demonstrate experiences of calming reported by students, teachers and researchers (Black & Fernando, 2013: Rix & Bernay, 2014and Milligan, et al, 2017. MBI's were found to ameliorate low-grade depressive symptoms and showed positive indications of the programme's effectiveness in reducing stress and enhancing well-being (Kuyken et al, 2013;Rix & Bernay, 2014).…”
Section: Journal Entriesmentioning
confidence: 95%
“…Teacher benefit in the form of stress reduction has been found in a number of studies e.g. Rix and Bernay (2014). Teachers are the 'keepers of the code' in the classroom.…”
Section: Classroom Climate and Potential Teacher Benefitmentioning
confidence: 99%
See 1 more Smart Citation